Populism with a Ph.D: education levels and populist leaders. Issue 3 (2nd September 2021) - Brühwiler, Claudia Franziska; Goktepe, Katherine
ABSTRACT: Whether we define populism as an ideology, an aesthetic style, or a political strategy, populism is directed against a perceived elite and academic expertise. Yet we have seen several cases of academics who have adopted a populist style in their political careers: Pim Fortuyn (The Netherlands), Pablo Iglesias (Spain), Bernd Lucke (Germany), Christoph Mörgeli (Switzerland), and Yanis Varoufakis (Greece). This article examines how these academic populists address this apparent contradiction by construing 'the people' and 'the elite', thus that it furthers their own political persona.